Online News Video Consumption: A comparison of six countries. Issue 5 (28th May 2018) - Kalogeropoulos, Antonis
Abstract : Online news video is becoming increasingly prominent in the websites of news organizations and social media platforms. Given that we have limited knowledge on online news video use, this study examines the consumption of online news video in six countries (Denmark, France, Germany, Spain, United Kingdom and United States), as well as how online video news use is correlated with other news behaviour patterns. Based on a comparative survey of news consumption, it is evident that online news videos are becoming increasingly prominent in most countries. In addition, the study showed that online news videos are seen both on the sites of news organizations but especially and increasingly off-site on social media like Facebook and video-sharing sites like YouTube. This research is a first attempt in understanding the audience of online news videos. The findings reflect the power of social media platforms in influencing news consumption habits.